7th International symposium on fish endocrinology special issue - Somoza, Gustavo Manuel (2013)
It was a real pleasure and privilege to welcome 207 delegates 6 from 28 countries to the Seventh International Symposium on Fish Endocrinology (7ISFE) organized in Buenos Aires City, Argentina from September 3 to 6, 2012. The main goal of the symposium was to bring together fish endocrinologists from over the world in order to promote debate, discussion and start new collaboration between the different research groups. The Symposium was held for the first time in the Southern Hemisphere and it was an opportunity for researchers, postdoctoral fellows and students from all over South America to show their results, and to interact with other experts in fish endocrinology. For many delegates it was their first visit to South America. The first ISFE was organized by Dr. Peter Pang, Dr. Richard (Dick) Peter and Dr. Martin Schreibman in 1988 at the University of Alberta, Edmonton, Alberta, Canada. Dr. Dick Peter also served as the founding president of the International Standing Committee. At the business meeting of the 1st ISFE, it was decided that subsequent meetings of the ISFE series were to be held once every four years and two years out of phase with the quadrennial ICCE series. Subsequent ISFE meetings were successfully held in France (1992), Japan (1996), USA (2000), Spain (2004) and Canada (2008) under the auspices of the International Standing, Local Organizing and Scientific Program committees. In the early 2000?s, the International Standing Committee also decided that the significant contributions of Dr. Dick Peter to the founding of the ISFE will be recognized by naming a plenary lecture series at the ISFE meetings to honor scientists for significant scientific contributions to the field of fish endocrinology as the Richard E. Peter Lecture, starting with the 5th ISFE in Castellón, Spain in 2004. The inaugural speaker of this lecture series was Dr. Dick Peter himself in Spain, and then Dr. Yoshitaka Nagahama at the 6ISFE meeting in Canada, and in this 7ISFE, the scientific and international committees selected Dr. Olivier Kah (France) for this plenary lecture. The topics at the Buenos Aires Symposium were: Evolution and origin of the peptide hormones and receptors: structure and function; Neuroendocrinology; Neuroendocrinology of Reproduction; Steroid/Thyroid hormones and receptors; Pituitary gland: Molecular and cellular endocrinology; Endocrine disruption; Endocrine control of ion and osmoregulation; Gonadal endocrinology; Endocrine regulation of feeding and growth; Developmental endocrinology and sex differentiation; Endocrine aspects of behavior; Fish Endocrinology in the Post-Genomic Era: from transcriptomics to transgenics; Endocrinology of stress; Aquatic biotechnology related to fish endocrinology. Also three Satellite Symposia were organized during the week-end previous to the Symposium: ??Endocrinology of Chondrichthyans??, ??Fish Neuroanatomy and Brain Evolution?? and ??Impact of climate change on fish endocrine systems?? organized by Drs. Cynthia Awruch, Matías Pandolfi and Leandro Miranda, respectively. Following the ??Terms of Reference for Lifetime Achievement Award in Fish Endocrinology?? 7 (seven) researchers were awarded at the 7ISFE in Buenos Aires. In alphabetical order they were: Dr. Gloria Callard (USA), Dr. Jean Joss (Australia), Dr. Hiroshi Kawauchi (Japan), Dr. Haoren Lin (Republic of China), Dr. Nancy Sherwood (Canada), Dr. Norm Stacey (Canada) and Dr. John Youson (Canada). The 7ISFE was sponsored by CONICET (the National Research Council of Argentina) and ANPCyT (Agency for Science and Technology of Argentina). The 7ISFE was possible because of the work of the Local Organizing Committee: Fabián Canosa, Juan Fernandino, Fabiana Lo Nostro, Leandro Miranda, Matías Pandolfi, Gustavo Somoza and Paula Vissio in close contact with the Scientific Committee: Silvia Arranz (Argentina), Cynthia Awruch (Argentina), Nicholas Bernier (Canada), Pedro Carriquiriborde (Argentina), José Miguel Cerdá-Reverter (Spain), Víctor Cussac (Argentina), Yann Guiguen (France), Keerikkatil Joy (India), Vance Trudeau (Canada), Denise Vizziano (Uruguay), Anderson Wong (China) and Silvia Zanuy (Spain), and the ISFE International Committee: Ching-Fong Chang (Taiwan), Abigail Elizur (Australia), Wei Ge (China), Hamid Habibi (Canada), Olvier Kah (France), Makito Kobayashi (Japan), Berta Levavi-Sivan (Israel), Carl Schreck (USA), Rüdiger Schulz (The Netherlands), Penny Swanson (USA), Yoshio Takei (Japan), Charles Tyler (UK) and Glen Van Der Kraak (Canada). We would also like to thank Ms. Silvina Ceriani and TTS Eventos for their help in the organization of the Symposium. The next Symposium, 8ISFE, will be held in Gothenburg, Sweden, in 2016. For more information please contact Björn Thrandur Björnsson (thrandur.bjornsson@bioenv.gu.se) at the Department of Biological and Environmental Sciences of the University of Gothenburg. For the present issue a selection of presenters were invited to submit either a review or an original research manuscript. All manuscripts were peer-reviewed through the usual rigorous process of General and Comparative Endocrinology. We thank the reviewers for their expert evaluations. A special thanks is also due to Dr. Bob Dores, Editor-in-Chief, and Kathy Padilla, Journal Manager-Elsevier, who made this Special Issue possible. We think that the quality and diversity of research topics presented bodes well for the future of Fish Endocrinology.